Detection of Trichodina sp. In Nile Tilapia (Oreochromis niloticus) Cultivated inTanjung Bunga Lake, Makassar City (Journal of Vocational Innovation, Achievement and Education, 2025)
Tilapia is the favorite freshwater fish that is widely cultivated in Indonesia.The problem experienced by many tilapia farmers is the emergence of disease attacks. Inadequate water quality and high density play a role in causing stress in fish and increasing the risk of disease. Changes in natural conditions such as temperature, pH, and DO (dissolved oxygen) can affect water quality. One of the diseases that often occur in tilapia in aquaculture with poor water quality is diseases caused by ectoparasites. One type of ectoparasite that commonly attacks tilapia is Trichodina sp. This study aims to determine the presence of Trichodina sp. ectoparasite infection in tilapia cultivated in Tanjung Bunga Lake, Makassar City. Sampling using random sampling method with a total sample size of 58 fish. Ectoparasite examination was performed on body surface mucus and gills using a microscope with 400x magnification. Detection results on tilapia samples as many as 58 fish found 50 (86.2%) positive tilapia samples infected with Trichodina sp. ectoparasites, including 40 (80%) positive samples in the body surface mucus and gills, 8 (16%) positive samples only in the gills, and 2 (4%) positive samples only in the body surface mucus. The range of water quality examinations at seven points had temperatures ranging from 29-31°C, pH 6, salinity 0 mg/L, DO 2.24-10.24 mg/L, nitrate 0.0141-0.1857 mg/L, nitrite 0.0451-0.5555 mg/L, and ammonia 0.0028-0.0096 mg/L. The results of this study reveal that farmed tilapia may be infected with the ectoparasite Tricodina sp.
Keywords: Ectoparasite; Lake; Tilapia; Trichodina sp.